The Hedging Effectiveness of Crude Palm Oil Future in Malaysia : Hedging Ratio Estimation, Maturity and Duration Effects - Hu, Shan (2013)
Since the trade of crude palm oil in Malaysia is highly active and the use of the commodity is mainly for expert rather than consumption, the commodity futures trading which was introduced in Malaysia in October 1980, especially high trading volume of the crude palm oil futures (FCPO) has made the Bursa Malaysia as the world's biggest palm oil futures trading hub and the FCPO has become the global benchmark for the crude palm oil market. Moreover, due to its two major economic purposes for the Malaysian traders; one is to provide an efficient price discovery mechanism for the palm oil industry and the other one is to act as a hedging mechanism against the risk of price volatility in the crude palm oil spot market, there is a superior concern on its hedging effectiveness in reducing the risk of the traders' portfolio in the crude palm oil spot market. Furthermore, a comprehensive view about its hedging performance which could also be affected by the futures maturities and the lengths of hedging horizon (hedging duration) should not be neglected. Therefore, this paper attempts to investigate the best minimum variance hedge ratio (MVHR) for the Malaysian FCPO using various econometric models and to examine the effects of maturities and hedging duration on the MVHR estimation and their corresponding hedging performance. By evaluating the hedging effectiveness based on the minimum-variance and risk-return framework, the results indicate that the OLS, B-VAR and B-VECM perform better than the DVEC M-GARCH with achieving highest risk reduction and mean return in the hedged portfolio. Moreover, by adopting the conventional OLS to examine the effects of four different maturities of the FCPO on the effectiveness of hedging, the empirical findings show that futures hedging is more effective when the near-month contract is used. They also reveal that the MVHRs are lower for near-month hedging. Finally, through analyzing the duration effects on the MVHRs and hedging performance using 9 different hedging horizons and the AutoRegressive Distributed Lag (ADRL) Cointegration Model, both short and long term MVHRs are simultaneously estimated. The empirical results indicate that the short term hedge ratios are significantly less than one and it tends to increase with the length of hedging horizon and the long term MVHR is found to be close to the naive hedge ratio of unity. Moreover, the hedging performance improves with the length of hedging horizon. Overall, the empirical findings of this study would have some important implications to those related parties. More importantly, for Malaysian government, they should contribute to reduce the basis risk and improve the effectiveness of FCPO hedging by reducing the intervention as well as the intervention policies in the crude palm oil market and pursuing crude palm oil market liberalization.